E-bikes to infrastructure communication for personal mobility solutions - Tan, Seng Eng (2017)
Electric bicycles are increasingly popular around the world due to their capability to provide mobility at a relatively low cost. However, this has led to increased safety concerns from transport authorities around the world as statistics in recent years have shown an increasing amount of electric bicycles related accidents which resulted in numerous fatalities. This report discusses the possibility of using Global Positioning System (GPS) and transport communication systems to reduce the likelihood of electric bicycle related accidents. By studying the infrastructure for communication in transport systems, it is possible to develop and implement features to enhance safety of the cyclists. One of the suggested ways is to make use of V2X (Vehicle-To-Everything) and Global Positioning System (GPS). The communication protocol for V2X is IEEE 802.11p, specifically designed for Intelligent Transport Systems. This project consists of concept generation, developing use cases, assessment of practicality and feasibility and lastly implementation. This is demonstrated through the use of a standalone smart device which may be embedded into the electric bicycle system in the future. As this project is done in collaboration with Groupe PSA, Europe's second largest automaker, this report will also consist of a short section which will briefly cover the cost/benefits analysis.